Role of Halal Digital Ecosystem and Msmes Strengthening in Jepara Toward Sustainable Economy in Industry 4.0 - Niswatin Nada; Agung Slamet Sukardi (Universitas Trunojoyo Madura, 2026)
This study examines the low level of digital literacy and limited understanding of halal certification among MSMEs in Jepara Regency and how this affects their ability to effectively utilizehalal certification in the digital era. This issue is highlighted by the low level of knowledge and use of halal certification among MSMEs in Jepara, both in understanding the certification process and in using it as a business development strategy. The findings indicate that government initiatives to promote digital transformation and halal certification have not yet been fully effective due to limited digital skills, inadequate human resources, and continued reliance on manual processes. Advances in Industry 4.0 technology and digital marketing have created opportunities for small and medium sized enterprises (SMEs) to increase their competitiveness and expand their market reach however, in practice, small businesses still face several challenges, particularly limited business funding, high halal certification costs, and difficulties in product packaging. The study also shows that collaboration among public institutions, certification facilitators, cooperatives, and MSMEs actors has strong potential to build an integrated digital halal ecosystem that supports business sustainability and regional economic development. This research provides a conceptual framework linking digital capability, certification readiness, and institutional collaboration as key drivers of MSMEs competitiveness. This framework provides a practical contribution to Jepara Regency in developing a digital based halal ecosystem strengthening strategy to enhance MSMEs competitiveness and market access.